(untitled) (Applied Biological Research, 2016)
Comparative diabetogenic potentials of alloxan, streptozotocin (STZ) and alloxan-streptozotocin cocktail in rabbits was investigated. ‘New Zealand White’ rabbits, 1-1.5 kg body weight (b.w.), were administered100 mg alloxan kg-1 b.w and 65 mg STZ kg-1 b.w, individually and 50 mg alloxan kg-1 b.w. and 35 mg STZ kg-1 b.w. cocktail, as single intravenous dose. Fasting blood glucose levels were monitored on day 0, 3, 5, and 7. Rabbits with fasting blood glucose levels > 200 mg dL-1 were considered diabetic. Alloxan caused early induction of sustained hyperglycaemia while relatively resistant rabbits revealed mild hyperglycaemia on day 3 followed by progressive recovery. In contrast, alloxan-STZ cocktail caused a progressive increase in hyperglycaemic animals upto 7 days. However, the overall diabetogenic efficiency was less than alloxan alone. The hyperglycaemia was mild to moderate when alloxan-STZ cocktail was used as compared to that induced by alloxan alone which resulted in moderate to severe hyperglycaemia. STZ failed to induce significant and sustained hyperglycaemia in rabbits. It may be concluded that low dose alloxan-STZ cocktail is a choice for the induction of diabetic rabbit model whereas rabbits appeared relatively resistant to diabetogenic effects of STZ. Further, spontaneous progressive recovery warrant extra caution in evolving and extrapolating results while using such models.